Determinants of Informal Worker Participation in BPJS Ketenagakerjaan Program in Indonesia - Irsyadul Fikri; Nurman Setiawan Fadjar (Journal of Development Economic and Social Studies, 2026)
The informal labor sector has unconsciously developed within the economy as a form of substitution for the unmet absorption of labor in the formal sector. As the informal sector continues to expand in Indonesia, informal workers frequently face issues such as exclusion from social protection schemes and uncertain wages. A considerable proportion of individuals employed in this sector remain without health insurance coverage, even though health is a fundamental asset in sustaining economic activities. The large number of informal workers necessitates the provision of adequate health and social security programs. This study aims to analyze the factors influencing the participation of informal workers in the BPJS Ketenagakerjaan program across 32 provinces in Indonesia using panel data regression analysis. The results indicate that wages have no significant effect on informal workers’ participation in BPJS Ketenagakerjaan. In contrast, internet usage and average years of schooling have a significant positive effect, while the number of people living in poverty has a significant negative effect on informal workers’ participation in the program.